Degree, duration, and causes of visual loss in uveitis. Issue 9 (17th August 2004) - Durrani, O M; Tehrani, N N; Marr, J E; Moradi, P; Stavrou, P; Murray, P I
Abstract : Background/aims: Uveitis is a major cause of visual morbidity in the working age group. The authors investigated the duration, degree, and causes of visual loss in uveitis patients with the aim of better defining the visual morbidity and identifying potential risk factors. Methods: A retrospective, non-interventional, observational survey of 315 consecutive patients attending a tertiary referral uveitis service. Results: The mean duration of follow up was 36.7 months. Reduced vision (⩽6/18) was found in 220/315 (69.95%) of the patients with a subset of 120 patients having vision ⩽6/60. Unilateral visual loss occurred in 109 (49.54%), while 111 (50.45%) had bilateral loss. The mean duration of visual loss was 21 months. Of the 148 patients with pan-uveitis, 125 (84.45%) had reduced vision, with 66 (53%) having vision ⩽6/60. Main causes of visual loss were cystoid macular oedema (CMO) (59/220, 26.8%), cataract (39/220, 17.7%), and combination of CMO and cataract (44/220, 20%). The following were predictive of a poorer visual prognosis: pan-uveitis (p = 0.0005), bilateral inflammation (p = 0.0005), increasing duration of reduced vision (p = 0.0005), an Indian or Pakistani ethnic background (p = 0.004), and increasing patient age (p = 0.02). Conclusion: Prolonged visual loss occurred in two thirds of uveitis patients, with 70 (22%) patients meeting the criteria for legal blindness at some point in their follow up. Older patients with bilateral inflammation and an increasing duration of reduced vision are at the greatest risk of severe visual loss (⩽6/60). CMO and cataract were responsible for visual loss in 64.5% of patients.